An Analysis Upon Various Modeling and Evolutionary Optimization of Big Data Analytics: An Overview of Modeling and Optimization Techniques in Big Data Analytics (Journal of Advances and Scholarly Researches in Allied Education, 2015)
In the recent times the amount of data aregenerated and stored by various industries are rapidly increasing on theinternet thus data scientists are facing a lot of challenges for maintaining ahuge amount of data as the fast growing industries require the significantinformation for enhancing the business and for predictive analysis of theinformation. This paper focuses on the various states of the studies towardsBig Data analytic techniques and gives a better comparative analysis of variousapplications proposed till date. Inference has been done for evaluating theperformance efficiency, limitations and the advantages of the different typesof existing Big Data Analytic techniques. The main objective of the proposedstudy is to provide a better and significant research perspective and anoverview of data analysis techniques which are referred to the papers found onthe web which will be quite helpful for the future research prospective of thisdomain.